Horse Antithymocyte Globulin as Salvage Therapy after Rabbit Antithymocyte Globulin for Severe Aplastic Anemia - Scheinberg, Phillip (2014)
The effectiveness of salvage therapy for aplastic anemia patients unresponsive to initial rabbit antithymocyte globulin (r-ATG) or cyclophosphamide is not known. We investigated standard horse ATG (h-ATG) plus cyclosporine (CsA) in patients who were refractory to initial r-ATG/CsA (n=19) or cyclophosphamide/CsA (n=6) (registered at clinicaltrials.gov as NCT00944749). The primary endpoint was hematologic response at 3 months and was defined as no longer meeting criteria for severe aplastic anemia. Of the 19 patients who received r-ATG as initial therapy, 4 (21%) achieved a hematologic response by 3 months, and of the 6 patients who received cyclophosphamide, only 1 (17%) responded at 6 months. Among responders there have been no cases of relapse, and in nonresponders 2 patients evolved to monosomy 7. The overall survival for the cohort at 3 years was 68% (95% CI, 50-91%). These results suggest that only a minority can be successfully salvaged after receiving as first therapy either r-ATG or cyclophosphamide. While h-ATG may be utilized in the salvage setting, the overall response rate likely will be lower than when h-ATG is used as initial treatment.